(untitled) (Journal of Human Sciences, 2022)
The family is the first social cell and social medium in which the individual is created and works on his comprehensive formation and its role in social control and sound education, as its impact is direct, deep and strong on its children, their personal formation and their psychological and social compatibility. The contribution of the family’s role is to protect its children from crime and deviant behavior on the grounds that it is the main institution of the socialization process, which works to instill sound social values and standards that constitute major social controls to reduce crime, which calls for protecting the family and working to strengthen family ties and roles and expedite their treatment. The main objective of the study is to identify the importance of the role played by the family in the prevention and protection of its children from crime, as well as to shed light on the concepts related to the family and crime, and therefore the study problem revolves in answering the following questions: - What are the social, educational, cultural, religious and economic roles that the family plays in Preventing and protecting her children from crime? What are the most important obstacles facing the family and impeding the exercise of these roles? To achieve this goal, an interview questionnaire was designed to collect primary data from a sample of heads of households that will be selected in a random manner consisting of 40 individuals from the Soukra locality of Sebha, using the descriptive approach of the research variables, and the results have been presented that will be presented later.